The Effectiveness of Partner Reading Strategy to Improve Students’ Reading Comprehension for Junior High School Students - Nur Fitri Anisa; Nafisah Endahati (JEdu: Journal of English Education, 2022)
The importance of the reading ability was demonstrated in the educational curriculum. In Junior High School, reading is one of the English skills that should be studied and mastered at every level of school according to Kurikulum 2013 (K13). It was mentioned in presentation of the Deputy Minister of Education and Culture of the Republic Indonesia, one of the points is students required to get used in reading and understand the text. But based on the observation at Junior High School 16 Yogyakarta, it was found that the students had low ability and motivation in reading. For that reason, it is necessary to provide strategy in teaching reading, teachers should pay attention to the strategy. So, the researcher conducts Partner Reading Strategy. Using two classes, the experiment class were taught by using partner reading strategy, and control class by using independent reading strategy. The result of the analysis showed that the students’ comprehension of reading text has improved. It was proven by the improvement of the score of students’ pre-test and post-test in the experiment class. It can be seen from the result of paired sample t-test. It is lower than 0,05 or 0,000 < 0,05. So, Ho was rejected and Ha was accepted. Besides that the result of students' reading comprehension of the control class differs from the experimental class. The control class resulted an average of 66 while the experimental class reached 82. It means that Partner Reading strategy affects the students’reading comprehension of eighth graders of SMP 16 Yogyakarta.